College Students' Learning Performance, Teaching Skills, and Teaching Innovation in Intercultural Communication Class: Evidence Based on Experiential Learning Theory - Zhang, Xueli; Cheng, Xiaoyan (Frontiers in Psychology, 2022)
In China, for the improvement of the learner performance is critical challenge for the teaching staff and the management in intellectual communication class. Indeed, the administration of the Chinese schools is failed to provide effective learning to the students with innovative methods. The objective of this study was to identify the role of college students learning performance, teaching skills, and teaching innovation in intellectual communication class. This study is based on the quantitative data collected on a five-point Likert scale from the target respondents who were students of different colleges and 700 questionnaires distributed for it. The study concludes that there is a significant relationship between abstract conceptualization, active participation, and reflective observation in students learning performance. Further, this study highlights that the mediating role of teaching innovation is critical for students learning performance. This study contributes to literature with a significant theoretical framework. Lastly, this study provides significant theoretical implications and practical implications that are key game-changers for improving the performance of the students in the intellectual communication class.